Tuberculosis of calcaneum: a case series and review of literature - Tiwari, Anurag; Bhatnagar, Nishit; Karkhur, Yugal; Aslam, Ammar; Sharma, Amit; Sabat, Dhananjaya (International Journal of Research in Orthopaedics, 2017)
Background: The purpose of this study was to review the cases of isolated tuberculous osteomyelitis of calcaneum in terms of clinical features, radiological features, treatment and outcome. Methods: Medical records of 9 patients (7 males and 2 females) aged 4 to 45 years (mean 21.33 years) who presented with isolated calcaneal tuberculous osteomyelitis were reviewed. Clinical features, laboratory tests result, findings of imaging modalities, and histopathological examination were noted. The location of involvement of tuberculosis and treatment offered were noted. Multifocal tuberculosis and articular involvement were excluded. Results: All patients presented with pain and swelling around the heel; three of them presented with a discharging sinus. Patients had involvement of calcaneal body (n=5), tuberosity (n=2), and anterior process (n=2). The erythrocyte sedimentation rate of all patients was elevated. All the patients were treated conservatively with immobilization and chemotherapy. Conclusions: Isolated calcaneal tuberculosis is rare and the prognosis with non-operative treatment is good.